Anthropometric and strength profiles of professional handball players in relation to their playing position - multivariate analysis - Lijewski, M.; Burdukiewicz, A.; Pietraszewska, J.; Stachon, A.; Andrzejewska, J.; Chromik, K. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: In team sports, the varied levels of physical demand associated with different field positions are reflected in the morphofunctional features of the players. The aim of this work was to recognize how the playing position in the team depends on the anthropometric profiles and the strength level of professional handball players. Methods: A body mass, stature, lower and upper extremity length, circumferences and skinfolds were measured in the male professional athletes. The body composition was analysed using a bioelectrical impedance method. Additionally, hand grip and back strength were measured. A statistical analysis was carried out using routinely statistic methods and principal component analysis. Results: Pivot players usually have the most athletic figure in terms of size and weight and relatively short legs. The backs are characterized by the android body type and low subcutaneous fat content, and a large mass of body cells. The backs and pivots have the same strength of back and hand grip. Goalkeepers have relatively long upper and lower limbs and high back and hand grip strength. The wingers are usually slender, have medium length limbs, low body fat percentage, significant extracellular mass and the lowest muscle strength. Conclusions: The results of the multivariate analysis were a notable and valuable addition to the study of morphological and strength differences in a group quite homogeneous like a handball team. The principal component analysis allowed for a reduction of the multidimensional structure to three variables describing body massiveness, strength, and the length and height aspect of the body.